Aesthetics of ambiguity and mystery in late 20th century Japanese posters - Nguyen, Hung Ky (Curtin University, 2014)
My thesis argues that ambiguity and mystery are the essence of late 20th century Japanese posters. Through the use of qualitative and 'thick description' approach my thesis explores late 20th century Japanese poster production from the five Japanese poster designers' points of view; appreciation of ambiguity and mystery in Japanese culture and in these designers' works; and the extent to which Japanese cultural references and East Asian Buddhist philosophy and aesthetics have influenced these designers.